Analysis of Factors Influencing Public Behavior Decision Making: Under Mass Incidents - Shi, Rui; Liu, Chang; Gull, Nida (Frontiers in Psychology, 2022)
Most mass incidents are created by economic or social concerns brought on by fast socioeconomic change and poor local government. The number of mass occurrences in China has significantly increased in recent years, putting the country's steady growth and public behaviour decision-making in harm. We examine the factors that influence public behaviour decision-making in the following significant factors, contributing to the development of effective prevention and response strategies. The structural equation (SEM) approach is used to analyze the main determinants influencing public behavioural decisions in the aftermath of mass incidents using surveys of a large population. The finding shows that media plays a mediating role in the relationship between mass occurrences and influencing factors impacting public emotion. The direct and indirect effects of public behaviour decision-making and its role increasingly social changes as things happen, government credibility, media plays mediating role in public emotional factors. All directly impact public behaviour decision-making, while emotional factors have an indirect impact via media intermediaries. The escalation of public behaviour decisions is seen as a result of structural transmission and the increase of dynamic as well as other factors.